Kalimat Imperatif Dalam Novel Ayah Dan Sirkus Pohon Karya Andrea Hirata - Lupyta, Destri; Ariyanti, Tri Dina; Yuniati, Ira; Hakim, Man (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The objective of this research to describe imperative sentences in the novel of Ayah dan Sirkus Pohon by Andrea Hirata. This novel tells the story of Sobirin, a 28-year-old unemployed man, and his winding journey in a traveling circus called Sirkus Blasia. The problem in this study is the imperative sentences in the novel of Ayah dan Sirkus Pohon by Andrea Hirata. This study was conducted using a qualitative descriptive approach. Data collection techniques used library research techniques. Data analysis was carried out through data reduction, data presentation, verification, and conclusions. The results of this study include imperative sentences of commands, imperative sentences of requests, imperative sentences of granting permission, imperative sentences of invitations, and imperative sentences of orders. The imperative sentences that frequently appear in Andrea Hirata's novel Ayah dan Sirkus Pohon is imperative command sentences with a total of 8 and the imperative sentences that appear the least are imperative permission and invitation sentences with the same number, namely 4. In the future, the author hopes that students of the Faculty of Teacher Training and Indonesian Language and Literature Education will increase their insight into literary studies.